2003
DOI: 10.1016/s0042-6989(03)00457-7
|View full text |Cite
|
Sign up to set email alerts
|

Visual perception in a blind subject with a chronic microelectronic retinal prosthesis

Abstract: A retinal prosthesis was permanently implanted in the eye of a completely blind test subject. This report details the results from the first 10 weeks of testing with the implant subject. The implanted device included an extraocular case to hold electronics, an intraocular electrode array (platinum disks, 4 x 4 arrangement) designed to interface with the retina, and a cable to connect the electronics case to the electrode array. The subject was able to see perceptions of light (spots) on all 16 electrodes of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
587
1
4

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 790 publications
(604 citation statements)
references
References 15 publications
12
587
1
4
Order By: Relevance
“…Human experiments using subretinal electronic implants have revealed that inner retinal components survive in end-stage retinitis pigmentosa and patients retain a retinotopic map if the retina can be stimulated appropriately. 1 It remains to be seen if transplanted sheets of foetal photoreceptors could wire-up sufficiently to replicate these effects.…”
Section: Generating Photoreceptor Cells From Foetal Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…Human experiments using subretinal electronic implants have revealed that inner retinal components survive in end-stage retinitis pigmentosa and patients retain a retinotopic map if the retina can be stimulated appropriately. 1 It remains to be seen if transplanted sheets of foetal photoreceptors could wire-up sufficiently to replicate these effects.…”
Section: Generating Photoreceptor Cells From Foetal Tissuementioning
confidence: 99%
“…Any strategy to restore sight in these cases would almost certainly require cell replacement or transplantation. Although significant developments have been made with electronic implants over recent years, 1 there will still need to be an interface between electronic hardware and biological tissues at some point along the visual pathway. This will be highly complex.…”
Section: Introductionmentioning
confidence: 99%
“…Determining with a normal cat model whether the current provided by the MPA device is sufficient to activate overlying retinal neurons is beyond the scope of this study. However, we should note that more recent studies have shown that current levels that produce visual sensations can damage tissue [27] and that low levels of current are sufficient for eliciting visual function [20] and visually evoked cortical responses [28].…”
Section: In Vivo Function Of Microphotodiode Array Devicementioning
confidence: 99%
“…Given this situation, a number of research groups have examined the possibility that a retinal prosthetic capable of transducing light into an electrical signal might restore visual function following photoreceptor degeneration. In fact, preliminary data from clinical trials approved by the U.S. Food and Drug Administration (FDA) suggest improved visual function in patients implanted with subretinal [19] or epiretinal [20] devices. Patients reported both subjective and objective improvements in visual function, including the ability to detect light and motion and recognize objects [19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation